Partnership of University and Schools Within the Preparation of Future Teachers - Galustyan, Olga Vladimirovna; Kirik, Vladimir Alexandrovich; Mazáová, Nataša (International Journal of Emerging Technologies in Learning (iJET), 2019)
The article analyzes partnership of university and schools within the preparation of future teachers. It deals with preparation of future teacher in order to master the project competence which is necessary for the implementation of future professional activities. The authors identify organizational, procedural, communicative, reflective components within the structure of project competence. The authors conclude that an important role plays organizing partnerships within the project activities during pedagogical practice of university students at schools.